2002
DOI: 10.1891/vivi.17.6.719.33718
|View full text |Cite
|
Sign up to set email alerts
|

Child Custody Evaluations and Domestic Violence: Case Comparisons

Abstract: The literature indicates that witnessing domestic violence is harmful to children, that them is a high overlap between domestic violence and child abuse, and that safety is an important issue for separating women because separation from abusive partners is a particularly dangerous time for victims of domestic violence. Further, child custody is often a contentious issue in domestic violence cases. Child custody evaluations are typically used to assist courts in deciding custody when custody is disputed and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 56 publications
0
32
0
1
Order By: Relevance
“…In addition to crafting PO stipulations to meet women's needs, more responsive enforcement and follow-up may be required depending on the situation. Previous studies of court actions in divorce and custody decisions suggests a need for closer consideration of specific case characteristicsparticularly violence history and child abuse secondary to partner violence (Logan, Walker, Horvath, & Leukefeld, 2003;Logan, Walker, Jordan, & Horvath, 2002). One policy recommendation that might be derived from this study is that a closer court involvement with parties to a PO may be indicated as required in divorce and custody cases.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to crafting PO stipulations to meet women's needs, more responsive enforcement and follow-up may be required depending on the situation. Previous studies of court actions in divorce and custody decisions suggests a need for closer consideration of specific case characteristicsparticularly violence history and child abuse secondary to partner violence (Logan, Walker, Horvath, & Leukefeld, 2003;Logan, Walker, Jordan, & Horvath, 2002). One policy recommendation that might be derived from this study is that a closer court involvement with parties to a PO may be indicated as required in divorce and custody cases.…”
Section: Discussionmentioning
confidence: 85%
“…Parents with a domestic violence history were as likely to be steered into mediation as those without, despite the inappropriateness of mediation in these cases. In addition, custody outcomes did not differ between families with and without this history (Logan, Walker, Jordan & Horvath, 2002).…”
Section: The Gap Between Theory and Practicementioning
confidence: 82%
“…The risk for continued intimate partner violence increases during the separation period . The risk of exposing children to domestic violence also increases during the separation period (Cuthbert et al, 2002;Logan et al, 2002). An interesting recent finding is that men who batter appear to score higher than men engaged in separation engendered violence on measures of negative attitudes toward women.…”
Section: Importance Of Research About Men and Research About Womenmentioning
confidence: 99%
“…We end by discussing a variety of factors evaluators may consider using when developing an evaluation protocol to assess allegations of domestic violence within the context of child custody disputes. doi:10.1300/J190v04n01_01 [Article copies avail-Over the past several years, the assessment of allegations of domestic violence in child custody 1 evaluations has been among the hottest topics for research and practice in both clinical and forensic psychology (Jaffe et al, 2003aJohnston & Campbell, 1993;Logan, Walker, Jordan, & Horvath, 2002;Meier, 2003) and is of great interest to family court judges (Jaffe et al, 2003b;National Council of Juvenile and Family Court Judges, 1999;Schafran, 2003). Forensic assessment of allegations of domestic violence when custody is in dispute presents a unique challenge to forensic evaluators not only because of the complexity of the psychological variables involved in a comprehensive examination but also because of the political and social dimensions involved in judicial decisions about domestic violence (e.g., Cuthbert, Slote, Driggers, Mesh, Bancroft, & Silverman, 2002).…”
mentioning
confidence: 99%